Rapid analysis of food raw materials adulteration using laser direct infrared spectroscopy and imaging. (July 2020) - da Costa Filho, Paulo Augusto; Cobuccio, Leonardo; Mainali, Dipak; Rault, Mathieu; Cavin, Christophe
Abstract: The objective of this study was to assess the application of the Laser Direct Infrared (LDIR) imaging system as a rapid screening technology for detection, identification, and semi-quantitation of adulterants in food ingredients. Forty-five samples of skimmed milk powder, thirty-one samples of soy protein isolate, thirty-five samples of chicken meat powder, thirty-two samples of pea protein isolate and six samples of wheat flour were dry blended adulterated with nitrogen-rich compounds and bulking agents at concentrations of 1.0–15.0% (w/w). In addition, ten samples of skimmed milk powder were wet blended with food adulterants at 5.0% and 10.0% (w/w) to check the LDIR performance when different fraudulent processes are applied. The results from this study shows that LDIR can be used as a rapid untargeted screening method that are independent of adulterants to detect, identify and semi-quantify food adulterants in dry blended samples. In most samples, the technology accurately identified all nitrogen-rich compounds and bulking agents present in the dry blended samples. In addition, the technology shows sensitivity of 82% for samples adulterated at 1% and sensitivity from 92% to 100% for samples adulterated at ≥ 5% economic adulteration. On the other hand, the detection and identification of food adulterants in samples prepared by wet blending process was more challenging than dry blended samples because mid-infrared technology may not be sensitive enough to detect adulterants if they are dissolved or if hidden within the particles. Highlights: Untargeted analysis of food adulterants using laser direct infrared imaging. Detection analysis of nitrogen-rich compounds and bulking agent in food materials. The sensitivity of the method for detecting nitrogen rich compounds can reach up to 99%. The method takes less than 7 min to screen over twenty-five food adulterants.